Using imagination in response to stress and uncertainty in the time of COVID-19: further validation of the Fantastic Reality Ability Measurement (FRAME) Scale - Rubinstein, Dori; O’Rourke, Norm; Lahad, Mooli (Frontiers in Psychology, 2023)
Fantastic reality ability (FRA) is defined as the capacity to use imagination in response to stress or trauma. With the emergence of COVID-19 and associated social restrictions, there has been an uptick in imagination use as a coping strategy. This has allowed us to further validate the Fantastic Reality Ability Measurement (FRAME) Scale at this time of stress and uncertainty. Initial exploratory factor analyses (EFA) suggested that FRAME responses are measured by four first-order factors. Using confirmatory factor analyses (CFA), this study set out to confirm this finding and to ascertain if: First-order factors are correlated; or map onto a second or higher-order, fantastic reality ability latent construct. Also, FRAME responses are compared to established scales to demonstrate concurrent and discriminant validity. In accord with previous research and theory, CFA results indicate that each four factors (coping, control, transcendence, playfulness), contribute significantly to the measurement of a higher-order FRA latent construct (N = 437 Israeli adults). We also report robust correlations between FRAME and measures of resiliency and imagination abilities of complexity, directedness and frequency. Both adaptive and maladaptive applications of imagination use in relation to stress are discussed with focus on those who could foster resiliency. The FRAME enables one to briefly measure imagination use in response to stress and could serve as part of questionnaire batteries measuring individual differences and clinical research. Future research should assess the stability of this instrument across different populations over extended periods, specifically those at risk for trauma.